41 Effect of grazing cotton crop residue versus Bermudagrass on performance and economic parameters in late gestation beef cows. (28th November 2020) - Davis, Dylan B; Hernandez, Shane r; Stewart, Lawton
Abstract: The residual lint, seed, and leaf remaining after cotton harvest was evaluated as a feedstuff to reduce the amount of hay fed to beef cows during early winter. A study was conducted utilizing 36 crossbred Angus cross cows (BW 491.04 kg) in late gestation. Cows were stratified by weight and randomly assigned to one of four groups, and each group was assigned to one of two treatments: Bermudagrass hay (Cynodon dactylon) (HAY), or cotton (Gossypium hirsutum) crop residue + Bermudagrass hay (COTTON). All cattle remained on their respective treatments for 30 d, and BW were recorded before and after the feeding period. Hand-grab samples were collected of cotton residue in each field to quantify residue available at the beginning of grazing. Available residue in the cotton groups were 783.17 kg/acre and 911.13 kg/acre. Core samples were collected from each bale of a single lot of hay. The same lot of hay was used for both treatments. Hay was offered ad libitum for the HAY treatment, and hay was offered to the COTTON treatment, starting on d 19. A completely randomized design was used and data were analyzed using a one way analysis of variance. The CP, NDF, and ADF values for hay and cotton residue were 12.3, 62, and 37%, and 23.5, 66, and 57%, respectively. Average daily gain (1.02 and 0.60 kg) and average weight change (34.5 and 20.4 kg) were higher (P < 0.003) for HAY compared to COTTON cows; however, their subsequent calving and breeding performance in the herd were not affected. Average daily hay disappearance for COTTON (5.90 kg/hd) was lower (P < 0.02) compared to HAY (17.19 kg/hd). Overall daily hay cost per head was lower (P < 0.01) for COTTON compared to HAY ($0.65 and $1.89, respectively). These data show that grazing cotton crop residue can reduce feed cost in late gestation beef cows.